Low loaded MoS2/Carbon cloth as a highly efficient electrocatalyst for hydrogen evolution reaction. (8th January 2022) - Shaker, Tayebeh; Mehdipour, Hamid; Moshfegh, Alireza Z.
Abstract: Active edge sites of MoS2 nanosheets exhibit promising futures for hydrogen evolution reaction (HER), comparable with remarkable performances of highly cost platinum. However, 3D structures of MoS2 suffer from a lack of high mobility and unexposed active sites which lower the electrocatalytic activity. In this study, we show that there is a balance between increasing the active sites on the one hand and managing the charge transfer to facilitate the reaction on the other hand, and achieving this balance increases the efficiency of the electrocatalyst tremendously. For this purpose, we directly attached exfoliated MoS2 nanosheets onto carbon cloth (CC) substrate as a 3D network of conductive fibers via electrophoretic deposition at different applied voltages and deposition times, without adding any binder. This strategy gives rise to superior exposure of active sites while still maintaining good charge transferability over the whole 3D structure. Thus, a trace amount of loaded catalyst is enough to reach the benchmark current density of 10 mA/cm 2 towards H2 production with a low overpotential of 137 mV vs. RHE. The Stability of the optimum structures under continuous operation was examined up to 50 min and further confirmed with 500 successive cyclic voltammetry (CV) sweeps. To understand the adsorption nature of hydrogen, density functional theory (DFT) was employed for the MoS2 /graphene in both cases of pristine and defected MoS2 . The results of hydrogen adsorption free energy calculations revealed that H adsorption on the S site is the most stable adsorption configuration and with increasing the MoS2 thickness, the MoS2 /graphene activity towards hydrogen evolution decreases. A similar trend is also observed for the defected MoS2 /graphene composite up to two-layer MoS2 and the activity remains the same for three-layer MoS2 . The experimentally observed charge transfer into the MoS2 upon adsorption of the hydrogen atom and water molecule is also confirmed by our DFT calculations. Highlights: Fabrication of low-loaded highly active MoS2 electrocatalyst. Binder-free electrophoretic deposition with scale-up potential. Optimizing deposition to keep active sites and charge transfer in balance. Understanding the origin of high electrocatalytic activity via DFT calculations.